2019
DOI: 10.1007/s00401-019-02071-3
|View full text |Cite
|
Sign up to set email alerts
|

Lewy-related pathology exhibits two anatomically and genetically distinct progression patterns: a population-based study of Finns aged 85+

Abstract: According to a generally accepted concept Lewy-related pathology (LRP) follows hierarchical caudo-rostral progression. LRP is also frequently present concomitantly with Alzheimer’s disease (AD), and it has been hypothesized that AD-associated LRP forms a distinct type of α-synucleinopathy, where LRP originates in the amygdala. The frequency of distinct forms of LRP progression types has not been studied in a population-based setting. We investigated the distribution and progression of LRP and its relation to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 47 publications
3
77
2
Order By: Relevance
“…It was high in diffuse neocortical LBD (44/49, 89.7%) and low in amygdala-predominant LBD (1/29, 3.4%). The amygdala variant is thought to be secondary to AD [ 67 , 69 ], and we use the term “olfactory-amygdala” because this type usually involves olfaction. AD with LB exhibits rare α-synuclein deposition in the ENS [ 4 , 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was high in diffuse neocortical LBD (44/49, 89.7%) and low in amygdala-predominant LBD (1/29, 3.4%). The amygdala variant is thought to be secondary to AD [ 67 , 69 ], and we use the term “olfactory-amygdala” because this type usually involves olfaction. AD with LB exhibits rare α-synuclein deposition in the ENS [ 4 , 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SOC model assumes that the quantity of ␣synuclein inclusions in a given nucleus or cortical region increases over time [20][21][22]. This gives rise to the phenomenon of gradients: the initially affected neurons tend to show the most severe pathology, and the most recently affected neurons have the lowest density of ␣-synuclein pathology.…”
Section: Overview Of the Soc Modelmentioning
confidence: 99%
“…We previously hypothesized that brain-first PD is equivalent to those postmortem cases with a limbic (amygdala) predominant profile of ␣-synuclein pathology, and that body-first PD is equivalent to a brainstem-predominant distribution of ␣-synuclein pathology [18,19,21,60,61]. The SOC model predicts that those postmortem cases with a brainstempredominant profile will tend to have more symmetric ␣-synuclein pathology compared with the more asymmetric pathology seen in limbic-predominant cases.…”
Section: The Human Connectome and The Soc Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…3 • Postmortem studies have reported two overarching types of Lewy pathology: a brain stem-predominant type with more pathology in the brain stem than more rostral structures and a limbic/amygdala-predominant type, with more pathology near the "center of the brain" compared with more caudal structures. 6 The authors also point to the lack of "gut-only" cases reported in the Arizona autopsies. This group screens the entire digestive tract with 10-15 tissue sections.…”
mentioning
confidence: 98%